APLIKASI PENDIDIKAN KECAKAPAN HIDUP ( LIFE SKILLS) BERBASIS PENDIDIKAN AGAMA ISLAM - Indarti, Sri; M. Nasor; Rina Setyaningsih (UNISAN JURNAL, 2023)
This study aims to determine the application of life skills (life skills) based on Islamic education. The type of research used by the author is a qualitative descriptive research method, emphasizing the power of direct field observation and then analyzing data from existing data sources. And the results of this study indicate that Islamic education and life skills are a component that cannot be separated, because both are a unified whole in relation to life. This research also shows that the concept of life skills can be used as a new direction in Islamic education, by integrating several aspects of life skills with Islamic education. From the results of this study it can be concluded that the application of life skills can provide abilities, abilities and skills to students both in the fields of information technology and religion. As a provision to live their lives, it is hoped that each student will have personal, rational, social, academic and vocational skills that are integrated in Islamic education.